Transgenic Introduction of a Glycolate Oxidative Cycle into A. thaliana Chloroplasts Leads to Growth Improvement - Maier, Alexandra; Fahnenstich, Holger; Von Caemmerer, Susanne; Engqvist, Martin K.; Weber, Andreas P.; Flügge, Ulf-Ingo; Maurino, Veronica G. (Frontiers in Plant Science, 2012)
A complete glycolate catabolic cycle was established in chloroplasts of the C3-model plant Arabidopsis thaliana by which one molecule of glycolate is completely oxidized within the chloroplast to two molecules of CO2. Genes coding for glycolate oxidase, malate synthase, and catalase were introduced into the nuclear genome of A. thaliana by step-wise transformation. Other genes required for a fully operational pathway are the endogenous NADP-malic enzyme and pyruvate dehydrogenase. Transgenic lines expressing the complete novel pathway produced rossettes with more leaves and higher fresh and dry weight but individual leaves were flatter and thinner than the wild type. The photosynthetic rates of the transgenic plants were higher on a dry weight and chlorophyll basis, but there were no differences in the compensation point. In addition, transgenic plants showed a lower glycine/serine ratio than the wild type indicating a reduction of the flux through the photorespiratory pathway. In this way, due to the increased oxidation of glycolate inside the chloroplasts, a photorespiratory bypass was created, which resulted in higher CO2 assimilation and enhanced biomass production.